Methoprene application and diet protein supplementation to male melon fly, Bactrocera cucurbitae, modifies female remating behavior. (28th December 2013) - ul Haq, Ihsan; Vreysen, Marc J. B.; Teal, P. E. A.; Hendrichs, Jorge
Abstract Methoprene (an analogue of juvenile hormone) application and feeding on a protein diet is known to enhance male melon fly, Bactrocera cucurbitae Coquillett (Diptera: Tephritidae), mating success. In this study, we investigated the effect of these treatments on male B. cucurbitae's ability to inhibit female remating. While 14‐d‐old females were fed on protein diet, 6‐d‐old males were exposed to one of the following treatments: (i) topical application of methoprene and fed on a protein diet; (ii) no methoprene but fed on a protein diet; (iii) methoprene and sugar‐fed only; and (iv) sugar‐fed, 14‐d‐old males acted as controls. Treatments had no effect on a male's ability to depress the female remating receptivity in comparison to the control. Females mated with protein‐deprived males showed higher remating receptivity than females first mated with protein‐fed males. Methoprene and protein diet interaction had a positive effect on male mating success during the first and second mating of females. Significantly more females first mated with sugar‐fed males remated with protein‐fed males and females first mated with methoprene treated and protein‐fed males were more likely to remate with similarly treated males. Females mating latency (time to start mating) was significantly shorter with protein‐fed males, and mating duration was significantly longer with protein‐fed males compared with protein‐deprived males. These results are discussed in the context of methoprene and/or dietary protein as prerelease treatment of sterile males in area‐wide control of melon fly integrating the sterile insect technique (SIT).